IMPLEMENTASI KURIKULUM ISLAM DAN LINGKUNGAN PENDIDIKAN YANG TERINTEGRASI DALAM MENINGKATKAN HASIL BELAJAR - Badratul Laela, Neng Linda (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
Integrated Islamic primary schools are seen to act as Anasirit Taghyiir (gene change), escorting and directing social and cultural change. In this case, researchers are interested in conducting research on Primary schools. The research methods that will be used are descriptive, qualitative, and empirical approaches to the theory of " development " as the primary basis theoretical. This research includes qualitative research because the nature of the data collected is qualitatively patterned. Techniques used are observations and interviews. Based on the results of research and discussion, we can conclude that: First, the model curriculum SDIT consists of a curriculum that comes from the Foundation of education providers and curriculum development themselves, sourced from interest SDIT Smart Syahida, coupled with the curriculum habituation sourced from School Network Islam. as well as the curriculum used SDIT Syahida Smart curriculum combines mone, more curriculum and curriculum Foundation; and Second, Model integrated Islamic school environment Smart Syahida. Have their standards for support learning take place to achieve maximum success in learning. Third, student learning outcomes are excellent. They are viewed from the cognitive, affective, and psychomotor. By implementing the environmental education curriculum, Islam has produced good learning success